Obesity-related knowledge, attitude, and practices among primary care physicians in China: a cross-sectional study - Tang, Jusumei; Chen, Haoyuan; Pi, Linhua (Frontiers in Medicine, 2025)
BackgroundObesity is a major global public health crisis but remains inadequately addressed during clinical encounters. In China, the primary healthcare system plays a vital role in managing chronic; however, the knowledge, attitude, and practice (KAP) of primary care physicians (PCPs) regarding obesity have not been previously described.MethodsThis cross-sectional study surveyed 240 PCPs in Southwest China using self-administered KAP questionnaires. The questionnaires assessed obesity-related KAP and were measured using SPSS software. Descriptive statistics and univariate analyses were used to analyze the data.ResultsIn total, 240 PCPs completed the survey. While the majority (75.0%) reported awareness of the adverse health effects of obesity, their attitudes toward obesity management were generally negative. Notably, significant gaps were found in both knowledge and practice. Obesity knowledge of PCPs and practice subscale scores were 45.9% and 23.1% of the corresponding optimal scores, respectively. Exposure to formal obesity-related training was associated with significantly higher scores in knowledge (3.95 ± 2.04 vs. 2.32 ± 2.16, p < 0.001), attitudes (4.59 ± 1.12 vs. 3.96 ± 1.18, p < 0.001), and practices (1.76 ± 1.06 vs. 1.25 ± 1.00, p = 0.001).ConclusionSubstantial gaps exist in the KAP of PCPs regarding obesity in Southwest China. Formal training appears to significantly improve obesity-related KAP and may enhance the primary care management of patients with obesity.